Do School Facilities Matter? : The Case of the Peruvian Social Fund (FONCODES) - Schady, Norbert Rüdiger, 1967- 1967- (The World Bank, 1999)
A revised version was published as The Allocation and Impact of Social Funds: Spending on School Infrastructure in Peru (with Christina Paxson). World Bank Economic Review 16 (2): 297-319, 2002. - Education projects of the Peruvian Social Fund (FONCODES) have reached poor districts and, to the extent they live in those districts, poor households. FONCODES has had a positive effect on school attendance rates for young children, but not on the likelihood that children will be at an appropriate school level for their age. Since its creation in 1991, the Peruvian Social Fund (FONCODES) has spent about US